2023
DOI: 10.1038/s41598-023-34027-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and validation of fatty acid metabolism-related lncRNA signatures as a novel prognostic model for clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is a main subtype of renal cancer, and advanced ccRCC frequently has poor prognosis. Many studies have found that lipid metabolism influences tumor development and treatment. This study was to examine the prognostic and functional significance of genes associated with lipid metabolism in individuals with ccRCC. Using the database TCGA, differentially expressed genes (DEGs) associated with fatty acid metabolism (FAM) were identified. Prognostic risk score models for genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…Research has shown that SNHG17 is intimately connected to the growth, invasion, migration, resistance to chemicals, and apoptosis of tumor cells, and head and neck squamous cell carcinoma patients whose SNHG17 expression was high had a significantly unfavorable prognosis [17]. Studies showed that lncRNA AC103706.1 is associated with fat metabolism, copper apoptosis, and prognosis in ccRCC [51,52]. However, the relationship between six SRlncRNAs and CSCs has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that SNHG17 is intimately connected to the growth, invasion, migration, resistance to chemicals, and apoptosis of tumor cells, and head and neck squamous cell carcinoma patients whose SNHG17 expression was high had a significantly unfavorable prognosis [17]. Studies showed that lncRNA AC103706.1 is associated with fat metabolism, copper apoptosis, and prognosis in ccRCC [51,52]. However, the relationship between six SRlncRNAs and CSCs has not been reported yet.…”
Section: Discussionmentioning
confidence: 99%
“…If Log2 FC (fold change) is greater than 1 or less than −1 (|log2 FC| > 1), we think that the gene is expressed significantly different in two risk groups. Furthermore, the false discovery rate (FDR) should be less than 0.05 [24,25]. Then, based on the Gene Ontology (GO) enrichment analysis, the Cellular Components (CC), Molecular Functions (MF) and Biological Processes (BP) between high-risk and low-risk groups were performed by the "clusterProfiler" package.…”
Section: Functional Enrichment Analysismentioning
confidence: 99%
“…In another study, DRLs including ZEB1-AS1, SNHG16, and ALMS1-IT1 were found to be highly expressed in colon adenocarcinoma samples, predicting prognosis and in uencing the response to immunotherapy and chemotherapy in patients 34 . Additionally, the upregulation of FOXD2-AS1 and AC002070.1 in the immune microenvironment of kidney renal cells suggests their potential role in disul dptosis in kidney renal clear cell carcinoma 35 . The identi cation of DRLs holds fundamental implications for unraveling the speci c mechanisms underlying oncogenesis and predicting the prognosis of HNSC.…”
Section: Introductionmentioning
confidence: 99%